Library Carpentry: software skills training for library professionals - Baker, James; Moore, Caitlin; Priego, Ernesto; Alegre, Raquel; Cope, Jez; Price, Ludi; Stephens, Owen; van Strien, Daniel; Wilson, Greg (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2016)
Librarians play a crucial role in cultivating world-class research and in most disciplinary areas today world-class research relies on the use of software. This paper describes Library Carpentry, an introductory software skills training programme with a focus on the needs and requirements of library and information professionals. Using Library Carpentry as a case study of the development and delivery of software skills focused professional development, this paper describes the institutional and intellectual contexts in which Library Carpentry was conceived, the syllabus used for the initial exploratory programme, the administrative apparatus through which the programme was delivered, and the analysis of data collection exercises conducted during the programme. As many university librarians already have substantial expertise working with data, it argues that adding software skills (that is, coding and data manipulation that goes beyond the use of familiar office suites) to their armoury is an effective and important use of professional development resource.